Supply Chain Performance Measurement in a Refractory Brick Industry - Dira Ernawati; Sinta Dewi; Ni Ketut Sari (Future Science, 2022)
Every company needs to optimize and improve its performance. Performance improvement strategies cannot be well formulated if there has never been a performance measurement itself before. Determining the overall condition of the company can be done by assessing the performance of the entire lines of the supply chain. The SCOR model is considered appropriate for complex supply chain activities because it has a measurement process of plan, source, make, deliver, and return. The scale for each process in the supply chain is different, so the Snorm De Boer normalization technique is applied to equalize the assessment units for each criterion. Based on the performance indicator (PI) calculation, six PIs scores are below the average performance. Those six Pis are raw material planning, production planning, planning cycle time, yield, product defect from production, and the number of equipment maintenance. The six PIs are assessment indicators for the planning process and production process, so an improvement of the management system for both activities is essential to be carried out immediately to improve overall supply chain performance.